Retreatment with immunotherapy in a patient with hepatocellular carcinoma who received immune checkpoint inhibitors after primary curative treatment: a case report - Wang, Tao; Tang, Fei; Li, Fenghui; Yin, Weili; Liang, Jing (Frontiers in Oncology, 2024)
Hepatocellular carcinoma (HCC) presents a malignant pathology known for its high early recurrence rate following curative treatment, significantly impacting patient prognosis. Currently, effective strategies to mitigate early HCC recurrence remain undetermined. In this report, we document a case of HCC managed with curative radiofrequency ablation (RFA), particularly in a patient facing a high risk of early recurrence due to a substantial tumor size. In an effort to forestall recurrence, immune checkpoint inhibitors (ICIs) were preemptively administered for 6 months post-RFA. Despite this, early recurrence ensued upon ICIs cessation. Traditionally, the approach to advanced HCC has been conservative, yet recent years have seen promising outcomes with ICIs in advanced HCC. However, research on ICIs retreatment is limited. In the short term, this patient experienced widespread metastases post-ICIs discontinuation, yet exhibited prompt regression upon ICIs reinitiation. Notably, this represents the initial documented instance of employing ICIs to forestall recurrence subsequent to curative RFA in HCC. Following ICIs discontinuation, diffuse recurrence with multiple metastases emerged, with successful resolution upon ICIs retreatment.